1970
DOI: 10.1001/archinte.1970.00310110113019
|View full text |Cite
|
Sign up to set email alerts
|

Uremic Toxins

Abstract: ResultsCalcium.-The intestinal absorption of calcium, studied in four dogs in¬ toxicated with methylguanidine, was found to be impaired in all (Fig 1).The skeleton of these animals was examined roentgenographically at the end of the intoxication period (four months) and revealed a mild décalcification. Definite conclusions on the possible effect of methyl¬ guanidine on bone mineralization, however, require further in¬ vestigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

1972
1972
1991
1991

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…Administration of U to chronic uremic patients on maintenance hemodialysis induced a clearly evident carbohydrate intolerance [21], and the same effect was induced in normal volunteers [22] and patients with mild renal failure to whom U had been given in such doses as to increase their plasma U levels to the values found in severe uremia [9]. Finally, carbohydrate intolerance was also induced in normal dogs intoxicated with U [7]. It seems quite likely that U plays a role in genesis of uremic intoxication -particularly in causing the carbohydrate intolerance typical of this condition.…”
Section: Effects O F Metabolites Known To Accumulate In Renal Failurementioning
confidence: 82%
See 1 more Smart Citation
“…Administration of U to chronic uremic patients on maintenance hemodialysis induced a clearly evident carbohydrate intolerance [21], and the same effect was induced in normal volunteers [22] and patients with mild renal failure to whom U had been given in such doses as to increase their plasma U levels to the values found in severe uremia [9]. Finally, carbohydrate intolerance was also induced in normal dogs intoxicated with U [7]. It seems quite likely that U plays a role in genesis of uremic intoxication -particularly in causing the carbohydrate intolerance typical of this condition.…”
Section: Effects O F Metabolites Known To Accumulate In Renal Failurementioning
confidence: 82%
“…Normal dogs, injected with high doses of MG, died within 15 days from anemia due to hemolysis and reduced red cell production, from gastric ulcers with bleeding, and from peripheral neuro pathy [6]. When lower doses were given to maintain the plasma MG levels of dogs as high as those of severe uremic patients, the same symptoms appeared though less severe [2], Administration of MG to dogs induced cer tain metabolic abnormalities, which are also typical of the uremic state: hypertrygliceridemia [7], inhibited intestinal absorption of calcium [7], increase in the plasma fibrinogen levels, and depressed fibrinolytic activity [8], and im provement of the carbohydrate intolerance in dogs with alloxan diabetes [9],…”
Section: Effects O F Metabolites Known To Accumulate In Renal Failurementioning
confidence: 99%
“…Similar intracellular changes may result from accumulation of methyl guanidine [26] and explain the selective increase in plasma triglyceride induced in nonuremic experimental animals following chronic administration of this toxin, which -along with urea and creatinine -accumulates in the chronically uremic state. Preliminary studies in a chronically uremic rat model, which like man develops hypertriglyceridemia, suggest that hepatic triglyceride production may be increased [27] and support the hypothesis that increased VLDL production contributes to hyperlipidemia in uremia.…”
Section: Lipid Metabolism In Uremiamentioning
confidence: 84%
“…This effect can easily be observed in rats [12] at plasma concentrations similar to those measured in uremic patients [1][2][3]6,11,18]. Previous data, while not excluding a proximal site of action, provide some indirect evidence for a distal site of action: in fact, it has been suggested that the amidino group of MG may be responsible for the potassium-spar ing effect which occurs in the distal tubule [12].…”
Section: Introductionmentioning
confidence: 93%